Pengabdian Masyarakat Desa Denai Lama: Membangun Kesadaran Peluang Agrowisata di Desa - Azra Zalikha; Gita Puspita Yoga; Melati Melati; Hendra Hermain (Asosiasi Dosen Akuntansi Indonesia, 2021)
Community service is an activity that aims to help certain communities in several activities without expecting any kind of imbalance. Agrotourism is a very important asset in contributing to regional income and an arena for creativity to introduce regional characteristics and products. The community should be aware of the potential of the area where they live as a place for agro-tourism. For this reason, it is important for local governments to use persuasive communication as a factor in educating local communities on the potential of villages as agro-tourism sites. This study aims to analyze the persuasive communication strategy carried out by the Denai Lama Village Government, communication barriers in the process of forming an agro-tourism awareness community, and offering persuasive messages and effective communication media that can be designed to form an agro-tourism awareness community. Religious moderation is a conception that can build a tolerant and harmonious attitude in order to strengthen the unity and integrity of the nation. This study uses a qualitative approach to obtain facts from the existing symptoms and seek factual information. The results showed that the main persuasive communication strategy carried out by the government was the formation of the mindset of the local community with the potential for agro-tourism in the area where they lived.